Research Progress of Gold Core-shell Structured Nanoparticles in Tumor Therapy. (November 2020) - Zhang, Ziyan
Abstract: In previous research, the role of gold nanoparticles in tumor photothermal therapy and radiotherapy has attracted the attention of researchers. However, its limited photothermal conversion efficiency and inevitable biological toxicity restrict its further application. With the development of the field of nanomaterials, researchers have discovered that combining gold into core-shell structured nanomaterials can exhibit many surprising properties and has great potential in the field of tumor therapy. This article systematically reviews the progress of gold core-shell structured nanomaterials in the field of tumor therapy in recent years. In this paper, the progress of gold-core-shell nanomaterials in the field of cancer treatment in recent years is reviewed systematically, and the characteristics, preparation methods and deficiencies of gold core-shell nanoparticles are introduced respectively. Although gold core-shell nanoparticles have a good application prospect due to their low toxicity and good biocompatibility, a lot of research work is still needed to solve the problems such as aggregation, photothermal conversion efficiency and large-scale production.